Salinomycin-loaded lipid-polymer nanoparticles with anti-CD20 aptamers selectively suppress human CD20＋ melanoma stem cells - Zeng, Yi-bin; Yu, Zuo-chong; He, Yan-ni; Zhang, Tong; Du, Ling-bo; Dong, Yin-mei; Chen, Huai-wen; Zhang, Ying-ying; Wang, Wu-qing (Acta pharmacologica Sinica, 2018)
Melanoma is the deadliest type of skin cancer. CD20＋ melanoma stem cells （CSCs） are pivotal for metastasis and initiation of melanoma. Therefore, selective elimination of CD20＋ melanoma CSCs represents an effective treatment to eradicate melanoma. Salinomycin has emerged as an effective drug toward various CSCs. Due to its poor solubility, its therapeutic efficacy against melanoma CSCs has never been evaluated. In order to target CD20＋ melanoma CSCs, we designed salinomycin-loaded lipid-polymer nanoparticles with anti-CD20 aptamers （CD20-SA-NPs）. Using a single-step nanoprecipitation method, salinomycin-loaded lipid- polymer nanoparticles （SA-NPs） were prepared, then CD20-SA-NPs were obtained through conjugation of thiolated anti-CD20 aptamers to SA-NPs via a maleimide-thiol reaction. CD20-SA-NPs displayed a small size of 96.3 nm, encapsulation efficiency higher than 60% and sustained drug release ability. The uptake of CD20-SA-NPs by CD20＋ melanoma CSCs was significantly higher than that of SA-NPs and salinomycin, leading to greatly enhanced cytotoxic effects in vitro, thus the ICso values of CD20-SA-NPs were reduced to 5.7 and 2.6 pg/mL in A375 CD20＋ cells and WM266-4 CD＋ cells, respectively. CD20-SA-NPs showed a selective cytotoxicity toward CD20＋ melanoma CSCs, as evidenced by the best therapeutic efficacy in suppressing＊the formation of tumor spheres and the proportion of CD20＋ cells in melanoma cell lines. In mice bearing melanoma xenografts, administration of CD20-SA-NPs （salinomycin 5 mg·kg^-1·d^-1, iv, for 60 d） showed a superior efficacy in inhibition of melanoma growth compared with SA-NPs and salinomycin. In conclusion, CD20 is a superior target for delivering drugs to melanoma CSCs. CD20-SA-NPs display effective delivery of salinomycin to CD20＋ melanoma CSCs and represent a promising treatment for melanoma.